2007
DOI: 10.2298/aci0702045t
|View full text |Cite
|
Sign up to set email alerts
|

Retroperitoneal endoscopic adrenalectomy vs. Conventional adrenalectomy in treatment of benign adrenal lesions: Comparative analysis

Abstract: Minimally invasive adrenalectomy is considered to be the standard of care for the surgical treatment of the adrenal gland' s pathology. Since the initial report of laparoscopic adrenalectomy in 1992 and of retroperitoneal endoscopic adrenalectomy in 1994, it has evolved into a feasible and safe minimally invasive procedure for benign adrenal tumors. Clinical characteristics and outcomes of 63 retroperitoneal endoscopic adrenalectomies (REAs) and 45 conventional adrenalectomies (CAs) from 1996 to 2004 were eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Since laparoscopic adrenalectomy was first described in 1992 by Gagner et al [1], this minimally invasive procedure has replaced open adrenalectomy as the standard operation for benign adrenal disease over the last two decades [2][3][4]. Although less invasive approaches, such as single-site access, natural orifice transluminal endoscopic surgery (NOTES) and robotic-assisted surgery, have been developed, several limitations, including further refinements in instrumentation and operative techniques, hamper the broad acceptance of these new techniques [14][15][16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since laparoscopic adrenalectomy was first described in 1992 by Gagner et al [1], this minimally invasive procedure has replaced open adrenalectomy as the standard operation for benign adrenal disease over the last two decades [2][3][4]. Although less invasive approaches, such as single-site access, natural orifice transluminal endoscopic surgery (NOTES) and robotic-assisted surgery, have been developed, several limitations, including further refinements in instrumentation and operative techniques, hamper the broad acceptance of these new techniques [14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…Since laparoscopic adrenalectomy was first described in 1992 [1], several studies have demonstrated that this minimally invasive procedure can achieve the same results as open surgical procedures with less trauma and lower mortality [2][3][4]. At present, it has been considered the gold standard for the treatment of benign adrenal disease [5].…”
Section: Introductionmentioning
confidence: 99%